25 years of technology use in policing - Ugwudike, Pamela (International journal of police science & management, 2024)
Technological innovations including artificial intelligence (AI) and cognate systems with accessible user interfaces are informing policing decision-making around the world. The systems form part of the ‘smart justice’ technologies increasingly replacing analogue modes of law enforcement such as paper-based information analysis. This article maps the evolution of technological innovations in policing over the past 25 years, that is, since the 1990s. The article situates its analysis within relevant socio-political contexts and discusses key prospects, impacts, and challenges.